BS9 KMT2C- a tetralogy of fallot candidate gene. (May 2019) - Borland, Shona; Tenin, Gennadiy; Williams, Simon; Monaghan, Richard; Baxter, Matthew; Ray, David; Abraham, Sabu; Keavney, Bernard
Abstract : Congenital heart disease describes a group of defects resulting from aberrant heart development. Tetralogy of Fallot is the most common cyanotic congenital heart defect. The causes of congenital heart disease are poorly understood. Histone modifying genes have previously been implicated in congenital heart disease. KMT2C is a histone modifying gene which contains a catalytic SET domain which methylates histone 3 lysine 4 regulating gene expression. We have previously identified 18 mutations in KMT2C in a whole-exome sequencing study of 829 non-syndromic tetralogy of Fallot patients. These mutations are absent in gnomAD and had a combined annotation dependent depletion (CADD) score of more than 20 indicating the variants are rare and likely deleterious. We have now investigated the role of this gene further in tetralogy of Fallot and heart development. KMT2C expression during heart development has been studied using RT-PCR and in situ hybridisation. Kmt2c is expressed throughout the mouse embryonic heart from embryonic day 11.5 to 14.5 which is the key developmental time period for heart development with respect to the defects observed in tetralogy of Fallot. In human embryonic hearts cDNA expression of KMT2C was also found between Carnegie stages 13 and 20 (equivalent stages to mouse E11.5-14.5). Heart defects have been characterised using a mouse model where the SET domain of KMT2C has been deleted resulting in a catalytically inactive protein being produced. In mouse embryos homozygous for the deletion, all embryos appear to have abnormal heart development and ventricular septal defects with or without an overriding aorta (found in seven out of ten embryos studied, shown in figure) are the most common defect indicating similarities to tetralogy of Fallot. Other defects seen in these hearts have included abnormal ventricular myocardium with resemblance to non-compaction and atrial septal defects. Overall this work demonstrates that KMT2C is a good candidate gene for tetralogy of Fallot, both due to its cardiac expression and the defects exhibited in mice where the SET domain is deleted. Conflict of interest: None